Efficacy of combined radiotherapy and anti‐programmed death 1 therapy in acral and mucosal melanoma. Issue 4 (13th February 2019) - Kato, Junji; Hida, Tokimasa; Someya, Masanori; Sato, Sayuri; Sawada, Masahide; Horimoto, Kohei; Fujioka, Mao; Minowa, Tomoyuki; Matsui, Yoshiyuki; Tsuchiya, Takaaki; Kitagawa, Mio; Nakata, Kensei; et al.
Abstract: Some studies showed that clinical response to immune check point inhibitors is lower in acral and mucosal melanoma than in cutaneous melanoma. Although the synergistic effect of radiotherapy (RT) and ipilimumab has been reported in patients with brain metastasis, the efficacy of combined RT and anti‐programmed death 1 (PD‐1) therapy for acral and mucosal melanoma is unclear. The present study aimed to evaluate the efficacy of combined RT and anti‐PD‐1 therapy for acral and mucosal melanoma. We retrospectively analyzed patients with acral or mucosal melanoma who were treated with anti‐PD‐1 and RT at Sapporo Medical University Hospital. In 10 patients (acral, 3; mucosal, 7), the response rate (RR) and the disease control rate (DCR) were 40% and 60%, respectively. As regards mucosal melanoma, four of the seven patients had achieved complete response + partial response, and three had progressive disease (RR = 57.1%). Meanwhile, two of the three patients with acral melanoma had stable disease and one had progressive disease (RR and DCR were 0% and 66.6%, respectively). Except for the patients treated with palliative RT for bone metastasis in the present study, the RR was 50% (4/8 patients), and the DCR was 75% (6/8 patients). Vitiligo developed after RT in five (50%) patients at a median duration of 2 months after RT. The clinical response and the high occurrence of vitiligo suggest that the combination of RT and anti‐PD‐1 therapy could be effective in some patients with mucosal melanoma.